The protective effect of Sambucus ebulus against lung toxicity induced by gamma irradiation in mice - Mohammad Karami; Seyed Sajad Ale-Nabi; Anahita Nosrati; Atefeh Naimifar (Mazandaran University of Medical Sciences, 2015)
The aim of present study was to investigate the potential antioxidant and lung protective activities of Sambucus ebulus (SE) against toxicity induced by gamma irradiation. Hydroalcoholic extract of SE (20, 50 and 100 mg/kg) was studied for its lung protective activity. Phenol and flavonoid contents of SE were determined. Male C57 mice were divided into ten groups with five mice per group. Only the first and second groups (as negative control) received intraperitoneally normal saline fluid. Groups 3 to 5 received only SE extract at doses of 20 mg/kg, 50 mg/kg and 100 mg/kg intraperitoneally; three groups were repeatedly injected for 15 days as chronic group. Groups 6 to 8 received a single-dose of gamma irradiation just 2 hours before irradiation as acute group. The ninth and tenth groups (as positive control) received only gamma rays. Animal was exposed whole-body to 6 Gy gamma radiation. After irradiation, tissue sections of lung parenchyma were examined by light microscope for any histopathologic changes. SE at doses 50 and 100 mg/kg improved markedly histopathological changes induced by gamma irradiation in lung. Lung protective effect of SE could be due to attention of lipid peroxidation. Our study demonstrated that SE as a natural product has a protective effect against lung toxicity induced by   gamma irradiation in animal.